Technical issues of grid connected renewable energy sources: A new areas of research - Mekhilef, Saad; Saleh, Y.I.; Ghazi, S.; Shadman, F. (2014)
With its ever-growing energy demand, the world has a great potential to utilize renewable energy resources towards a more secure energy future. Renewable energy will play an important role in meeting high-energy demand growth and in addressing environmental concerns from the increase in fossil-fuelled power generation. However, the potential for a large-scale shift from the use of fossil fuels to renewable energy for electricity generation remains a highly debated issue in many countries. This is not without reason, as large-scale implementation of renewable energy will pose significant challenges to legacy power systems due to temporal fluctuations, geographical dispersion of renewable energy sources and inadequacy of the existing power grid. The paper will focus on potential new areas of research with relation to technical constrains of integrating renewable energy sources into the grid and analyze the different measures, strategies and policies used by different countries and governments to address the issues related to the grid connected renewable energy systems. In addition, existing barriers that limit the large-scale deployment of renewable energy sources, as well as possible solutions to overcome them.